The problem of differentiating ideology and politics in the context of the relationship between the motherland and the state. - Demirtshyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
Due to the historical fate of the Armenian people, issues related to the relationship between the borders of the homeland and the state have received great theoretical and practical resonance in the context of modern geopolitical transformations. The problem is that the historical homeland and the political homeland (state) of the Armenian people do not coincide either territorially or in terms of content. At the same time, the moral and aesthetic absolutization of the historical homeland has created an ideal, which embodies the past, in comparison with which the political homeland with its troublesome everyday life, endless problems and new challenges loses its attractiveness and value for many. In this regard, in order to understand the essence of the problem and to outline possible solutions, the concepts of transgression and transcendence acquire a new meaning and significance. Transgression, in our case, does not characterize the expansion of one’s own cultural boundaries, but the direction of the search for a more «stable» being (life) beyond its borders in other socio-cultural and civilized spaces. The second concept - transcendence, expresses a mythical, eternally relevant and primary representation of the historical homeland, which sometimes obscures the relevance of the life problems facing the state and the need to solve them.